Effect of Dipeptidyl Peptidase-4 Inhibitors on Bone Metabolism and the Possible Underlying Mechanisms - Yang, Yinqiu; Zhao, Chenhe; Liang, Jing; Yu, Mingxiang; Qu, Xinhua (Frontiers in Pharmacology, 2017)
Diabetes mellitus has been demonstrated to be closely associated with osteoporosis. Accordingly, hypoglycemic therapy is considered effective in treating metabolic bone disease. Recently, the effects of dipeptidyl peptidase-4 (DPP-4) inhibitors, a new type of antidiabetic drug, on bone metabolism have been widely studied. This review mainly describes the effects of DPP-4 inhibitors on bone metabolism, including their effects on bone mineral density, bone quality, and fracture risk. In addition, the potential underlying mechanisms are discussed. Based on the current progress in this research field, DPP-4 inhibitors have been proved to reduce fracture risk. In addition, sitagliptin, a strong and highly selective DPP-4 inhibitor, showed its beneficial effects on bone metabolism by improving bone mineral density, bone quality, and bone markers. With regard to the potential underlying mechanisms, DPP-4 inhibitors may promote bone formation and reduce bone resorption through DPP-4 substrates and DPP-4-related energy metabolism. Vitamin D and other related signaling pathways also play a role in affecting bone metabolism. Although these assumptions are controversial, they provide a translational pharmacology approach for the clinical use of DPP-4 inhibitors in the treatment of metabolic diseases. Prior to the use of these drugs in clinic, further studies should be conducted to determine the appropriate type of DPP-4 inhibitor, the people who would benefit the most from this therapy, appropriate dose and duration, and the effects of the treatment.